Deskripsi Keterampilan Berpikir Tingkat Tinggi (HOTS) Peserta Didik Menggunakan Model Guided Inquiry Pada Materi Hukum Dasar Kimia - Yeltri Mairoza; Zonalia Fitriza (Edukimia, 2021)
This study aims to describe the HOTS of students use a guided inquiry model on the basic laws of chemistry. This research is a library research, and the type of library research used is semi-systematic. Sources are secondary data from reputable scientific journals. The documentation method was used in collecting data and data analysis techniques used the Miles and Huberman method. Data analysis activities in the miles and huberman method consist of data reduction, data presentation, and conclusions. Based on the results of the journal review, it is concluded that the guided inquiry model can increase the HOTS of students and can be seen in the exploration, concept formation, application and closing stages of how to use the guided inquiry model in bringing out students HOTS on basic law of chemistry.